2016
DOI: 10.2106/jbjs.rvw.o.00007
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Genetic Predisposition to Frozen Shoulder?

Abstract: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 45 publications
0
32
0
7
Order By: Relevance
“…In particular, familiarity was investigated by collecting twin and familial clustering studies. 31 In the same study, the authors also performed a meta-analysis of immunological researches, which investigated the role of human leukocyte antigen (HLA)-B27, a protein involved in triggering the inflammatory response, as a risk factor for SS. Although unbiased genetic approaches were lacking and insufficient to definitively confirm this hypothesis, a significantly higher rate of HLA-B27 positivity in patients with idiopathic SS as compared with controls was reported, suggesting a genetic link with this condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, familiarity was investigated by collecting twin and familial clustering studies. 31 In the same study, the authors also performed a meta-analysis of immunological researches, which investigated the role of human leukocyte antigen (HLA)-B27, a protein involved in triggering the inflammatory response, as a risk factor for SS. Although unbiased genetic approaches were lacking and insufficient to definitively confirm this hypothesis, a significantly higher rate of HLA-B27 positivity in patients with idiopathic SS as compared with controls was reported, suggesting a genetic link with this condition.…”
Section: Introductionmentioning
confidence: 99%
“…Although unbiased genetic approaches were lacking and insufficient to definitively confirm this hypothesis, a significantly higher rate of HLA-B27 positivity in patients with idiopathic SS as compared with controls was reported, suggesting a genetic link with this condition. 31 …”
Section: Introductionmentioning
confidence: 99%
“…In the same review, the authors also investigated HLA-B27 and the risk of adhesive capsulitis through a meta-analysis. They found a significantly higher rate of HLA-B27 positivity among patients with idiopathic adhesive capsulitis than in controls [20]. HLA-B27 is a protein involved in inflammatory responses, and patients with ax-SpA have a high HLA-B27-positive rate.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding familial clustering, previous studies found a positive family history in first-degree relatives associated with adhesive capsulitis [19]. Authors of a recent systematic review investigated the association of adhesive capsulitis with family history and race by collecting twin and familial clustering studies; they found a genetic association in adhesive capsulitis [20]. In the same review, the authors also investigated HLA-B27 and the risk of adhesive capsulitis through a meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…it usually appears in females aged 40-60 and affects the dominant hand [66]. other researchers record higher predilection in white patients, patients with a positive family history and with a positive Hla-b27 antigen [68]. the course of the disease may be acute (< 6 weeks), subacute (6-12 weeks) or chronic (> 6 months).…”
Section: C) Palpitation Examinationmentioning
confidence: 99%